The book of loss - Jedamus, Julith; Weidenfeld & Nicolson (London : Weidenfeld & Nicolson, 2005)
In imperial tenth-century Japan, a renowned storyteller and lady-in-waiting to the empress is caught in a bitter rivalry with another woman for the love of a banished nobleman.
Adult
Keywords: Women -- Japan -- Social conditions -- Fiction; Historical fiction; Japan -- History -- Heian period, 794-1185 -- Fiction; Japan -- History -- 0-1868 -- Fiction